QUALIDADE DE VIDA EM CAMINHONEIROS: UMA REVISÃO SISTEMÁTICA DE LITERATURA - Prates Lourenço , Eduarda; Bogoni Budib Hashiguchi, Mariana; Henrique Amelio Alves Ferreira, Pedro; Dalla Vechia, Vinícius; Doro Lerco , Amandha; Lucca Caliani Juliani , Gean (ANAIS DO ENIC, 2026)
-